Os efeitos da crise econômica brasileira de 2014-2016 sobre o prêmio salarial por nível de escolaridade - Costa, Lara Maria Silva (2019)
The recent stage of recession in the economic cycle of Brazil, dating between second quarter of 2014 and fourth quarter of 2016 according to the Economic Cycle Dating Committee (Codace), has been pointed out by literature as one of the worst in the country's history, demarcated by long duration and intense severity. In the same sense, structural indicators of the labor market have reported record growth in the underutilization of labor rate and increase tendency in informality, sector with job conditions precarious if compared with the regulated market. In this context, this dissertation investigates the impacts resulting from the economic crisis on the determinants of wage premium, using data from Continuous Pnad from 2013 to 2017, in order to verify, above all, the variations in the return associated with the level of education, understood in the literature, as the individual characteristic that has the greatest weight in explaining yields. We also observe the behavior of wage differences between levels of education, given their relationship with income inequality. The empirical analysis was performed by applying the two-stage ordinary least squares regression method proposed by Heckman to treat the sample selectivity problem. The results show that workers with complete higher education were the ones that suffered more salary reductions in the analyzed period, while the lower schooling ones, with lower reserve salary, were less susceptible to real losses. This negative pressure on higher wages had as an additional consequence the reduction of wage differences among workers according to educational level, accompanied by losses to the general income of the population.